Branched Sulfonated Polyimide/Sulfonated Methylcellulose Composite Membranes with Remarkable Proton Conductivity and Selectivity for Vanadium Redox Flow Batteries. Issue 4 (29th January 2020) - Long, Jun; Yang, Hongyan; Wang, Yanlin; Xu, Wenjie; Liu, Jun; Luo, Huan; Li, Jinchao; Zhang, Yaping; Zhang, Hongping
Abstract: A series of branched sulfonated polyimide (bSPI)/sulfonated methylcellulose (s‐MC) composite membranes composed of a designed and synthesized bSPI polymer and functionalized s‐MC are prepared by using a facile solution casting method for vanadium redox flow batteries (VRFBs). Among all bSPI/s‐MC composite membranes, the optimized bSPI/s‐MC‐20 % composite membrane has the best proton selectivity of 2.45×10 5 S min cm −3, which is 14.4 times as high as the Nafion 115 membrane. The bSPI/s‐MC‐20 % composite membrane possesses superior proton conductivity compared to most reported SPI‐based composite membranes for VRFBs. The VRFB with a bSPI/s‐MC‐20 % composite membrane shows excellent battery efficiencies ( CE =99.2–98.0 %, EE =66.3–77.6 %) and capacity retention (73.3–47.2 %). Moreover, the cost of the bSPI/s‐MC‐20 % composite membrane is only a quarter of that of a commercial Nafion 115 membrane. This work develops a new strategy to fabricate cheap bSPI‐based composite membranes by introducing a suitable functionalized biomass material. Abstract : Branching out : A series of branched sulfonated polyimide (bSPI)/sulfonated methylcellulose (s‐MC) composite membranes are prepared for vanadium redox flow batteries (VRFBs). The cost of the bSPI/s‐MC‐20 % composite membrane is only a quarter of that of a commercial Nafion 115 membrane. Besides, a VRFB with the bSPI/s‐MC‐20 % composite membrane exhibits excellent battery efficiencies and cycling stability.